Holographic quantum liquids - Kaplis, N (2013)
In this thesis, applications of Holography in the context of Condensed Matter Physics and in particular hydrodynamics, will be studied. Holog- raphy or gauge/gravity duality has been an enormously useful tool in studying strongly-coupled Field Theories with particular success in their low-frequency and large-wavelength fluctuation regime, i.e the hydrody- namical regime. Here, following a phenomenological approach, gravita- tional systems, simple enough to be properly examined, will be studied in order to derive as much information as possible about their dual theories, given that their exact form is not accessible in this way. After a review of the most important elements of standard Condensed Matter Theory, the gauge/gravity duality itself will be presented, along with some of its most important achievements. Having established the framework of this work, the main results of this thesis will be presented. Initially the sound channel of the theory dual to the anti-de Sitter Reissner–Nordstro ̈m black hole space-time will be studied, at finite temperature and finite chemical potential. Hydrodynamical properties of the boundary theory will be of major interest. Following that, focus will be shifted towards another grav- itational system, namely the Electron Star. There, the shear channel of the dual theory will be mainly examined. The goal will be, as before, to extract information about the hydrodynamical properties of the boundary theory.